2020
DOI: 10.1186/s12872-020-01479-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of late reperfusion in ST-segment elevation myocardial infarction: a real-world retrospective cohort study

Abstract: Background Early reperfusion of the coronary artery has become the first choice for patients with ST-segment elevation myocardial infarction (STEMI). How to deal with patients who miss the time window for early reperfusion is still controversial. Based on real-world data, this study was conducted to explore whether percutaneous coronary intervention (PCI) has an advantage over standard drug therapy in patients who miss the optimal treatment window. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…AUC values close to 1 indicate a high-quality model with good separability. AUC value nearing 0 indicates a poor model, which has the least separability [33]. Additionally, the model has no capacity for class separation when the AUC is 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…AUC values close to 1 indicate a high-quality model with good separability. AUC value nearing 0 indicates a poor model, which has the least separability [33]. Additionally, the model has no capacity for class separation when the AUC is 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…There are several possible explanations for these findings. First, from a pathophysiological point of view, residual coronary antegrade flow and retrograde collateral circulation after MI ensures the survival of hibernating and stunned myocardium, and rescue of these cardiomyocytes can prevent myocardial remodeling and electrophysiological disorders [ 9 ]. Second, it has been proposed that patients with STEMI who present later (S2BT delay) are at a lower risk than those who present earlier because they have passed the initial high-risk period [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no standard criteria for dividing the timing of late and very-late revascularization. This study used 7d as the dividing point of late and very-late revascularization based on several clinical studies [ 9 , 16 , 17 ], which also used 7d as the dividing point and suggested that the clinical outcomes of patients with STEMI undergoing PCI within 7d and after 7d of onset might be different.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pri donošenju odluke o tretmanu ovih bolesnika, u obzir bi trebalo uzeti i intermitentnu, ili delimičnu okluziju koronarne arterije, stepen kolateralne cirkulacije, ishemijsko prekondicioniranje i metabolički status unutar područja ishemije. Sve ovo su faktori od značaja kada je u pitanju planiranje adekvatnog tretmana ovih pacijenata [15].…”
Section: Diskusijaunclassified